Effect of System Parameters and Cutter heads on Processing of Water Hyacinth - Mathur, S M; Jadhav, Santosh Kumar (Journal of Agricultural Engineering, 2009)
The effect of two system parameters namely, cutter head speeds and feed rates on compression characteristics of water hyacinth viz percent reduction in volume and weight were studied. The cylindrical cutter with shear bar gave maximum volume reduction of 80 percent at the maximum cutter head speed and feed rate of 14.39 m/s and 2.1 t/h, respectively.